(untitled) (Bangladesh Journal of Agricultural Research, 2015)
The study was carried out to assess the larvicidal efficacies of some indigenous plant seed extracts against epilachna beetle, Epilachna vigintioctopunctata in the laboratory of the Department of Entomology, HSTU, Dinajpur, Bangladesh. Petroleum ether and methanol solvent extracts of ata (Annona squamosa), neem (Azadirachta indica), dhutura (Datura metel) and castor (Ricinus communis) seeds were evaluated for their larvicidal properties against the larval stage of E. vigintioctopunctata. The result revealed that all the tested plant extracts had more or less insecticidal effect against the larvae and their progeny. Among the plant extracts, ata seed extract in methanol solvent performed the highest toxicity (LD50 value 0.031 mg/insect) in larval stage after 72 hours exposure time. The effects of the extracts on fecundity, fertility and F1 adult emergence of the epilachna beetle at doses 4.0, 2.0 and 1.0 ml/l of water including untreated control were also evaluated. The result indicated that, among the extracts, ata seed extract at maximum dose (4.0 ml/l water) showed the highest efficacy with the inhibition of total eggs (74.1%), viable eggs (80.4%) and number of emergent adult progeny (87.3%). The result also revealed that the number of eggs, number of viable eggs and F1 progeny production decreased with the increase of doses. All the treated doses effectively reduced the epilachna beetle as compared to untreated control. Bangladesh J. Agril. Res. 40(3): 451-463, September 2015